(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Ampelocissus barbata (Wall.) Planch. is a native medicinal herb in Bangladesh. The present study was aimed at exploring the phytochemical compositions and analgesic potential of the plant in vivo. The methanol extract of A. barbata along with its different fractions were subjected to phytochemical evaluation through established chemical tests for ascertaining the available pool of secondary metabolites within the plant. Eventually, the presence of at least eleven classes of phytoconstituents viz. alkaloids, flavonoids, phenolics, glycosides, saponins, starch, phytosterols, coumarins, tanins, resins and quinones were demonstrated. Among the four partitonates, ethyl acetate soluble fraction of A. barbata illustrated the maximum types of secondary metabolites qualitatively. The ability of the crude methanol extract (MEAB) and its ethyl acetate soluble fraction (EAAB) to suppress nociception both centrally and peripherally were investigated in Swiss albino mice by tail immersion method and acetic acid-induced writhing method, respectively. At the 90th minute of the tail immersion study, both MEAB and EAAB administered at the doses of 250 and 500 mg/kg body weight (MEAB1, MEAB2, EAAB1, EAAB2) exhibited 240.41%, 285.34%, 302.83% and 339.60% elongation of pain response, respectively, in comparison to the standard, pentazocine which effectuated 421.36% elongation at the same mark. Moreover, the test samples at the same doses as before exhibited reduction of pain sensation by 66.81%, 74.08%, 76.81%, and 83.52%, respectively, in the acetic acid-induced writhing response in mice. Both the central and peripheral analgesic potentials of EAAB were discernibly higher than those of MEAB at both doses. The findings of the study represents the pharmacological potential of this species in appropriate animal model for the first time and provides valid foundation to warrant future scientific endeavors into the plant. Bangladesh Pharmaceutical Journal 24(2): 117-124, 2021